Developing English Materials Based on Saintific Approach through Islamic Content for Islamic Senior High School Students - Arif Rahman; Masnayadi Masnayadi; Nerim Nerim; Muslim Muslim (Universitas Pendidikan Mandalika, 2019)
This curent study conducts research and development aiming to developed an appropriate English Instructional materials for Islamic characters based on saintific approach in 2013 Curriculum. Futhermore, this study were carried out at second and the third grade of Islamic Junior High School Mataram with total number 30 students involved as well as participants. In the phase of obtaining information, needs analysis and trying out, this study utilized a reserch and development study with saintific approach i.e. observing, associating, experimenting, associating and communicating. This study utilized needs analysis as main instrument in composing the English instructional materials through Scientific Approach, official approach of 2013 Curriculum. The product of the study shows that an English textbook, the four major skills of english were balance improved,i.e. listening, speaking, reading and writing. All of the materials are appropriate with the saintific aprroach in 2013 Curriculum and the contents refer to students’ Islamic character. The materials are for second and thisd grade of Islamic junior hihg School which are laid out into seven units. To summ up, the laid out and composition of the english material were developed based on Scientific Approach in term of steps and exercises of learning materials.